Study on the factors that influence women involvement in entrepreneurship: A case study in Melaka Tengah / Nur Hidayah Zool Kapli and Nur Lyana Hassan - Zool Kapli, Nur Hidayah; Hassan, Nur Lyana (Faculty of Administrative Science and Policy Studies, 2012)
The study seeks to determine the factors of women involvement in entrepreneurship. A sample of 139 women’s entrepreneur at Melaka Tengah district had been selected for this study. The findings showed that the independent variables or factors that support our hypothesis are motivation and government policies. It means that not all of these three factors determine their relationship with the factors of women involvement in entrepreneurship. Purposive sampling will be used to distribute the questionnaire to selected respondents. Based on this finding, motivation be the most contributor to the factors of women involvement in entrepreneurship. While, two out of three independent variables have a significant relationship with the factors of women involvement in entrepreneurship. This is due to the result of correlation coefficient that has been used. In conclusion, motivation and government policies contribute to the factors of women involvement in entrepreneurship.